Molecular Docking and Dynamics of Xylocarpus granatum as A Potential Parkinson’s Drug Targeting Multiple Enzymes - Irsal, Riyan Alifbi Putera; Gholam, Gusnia Meilin; Firdaus, Dzikri Anfasa; Liwanda, Novian; Chairunisa, Fernanda (Borneo Journal of Pharmacy, 2024)
Parkinson's disease is a global health challenge affecting over 10 million individuals worldwide, leading to increased disability-adjusted life years (DALYs) and a rise in mortality rates. This study explores the potential anti-Parkinson's properties of Xylocarpus granatum, focusing on its interaction with key enzymes associated with the disease: catechol-O-methyltransferase (COMT), adenosine A2A receptor (A2AR), and monoamine oxidase-B (MAO-B). Using molecular docking and molecular dynamics approaches with YASARA Structure, the ethanol extract of X. granatum was investigated for its mechanism of action. Among 30 compounds, five demonstrated promising binding affinities. Structural flexibility analysis revealed minimal fluctuations in active-site residues, highlighting the stability of key complexes involving kaempferol, epicatechin, epigallocatechin, and native ligands. Molecular Mechanics Poisson–Boltzmann Surface Area (MM-PBSA) simulations provided insights into the binding energy of these complexes. Notably, kaempferol exhibited higher binding energy than the natural ligand, suggesting superior binding affinity. Analysis of the average radius of gyration (Rg) showcased control drug-MAO-B exhibited higher Rg values, indicating a more flexible protein conformation. Confirming mode stability with root mean square deviation (RMSD) analysis shows overall stability, except in the A2AR-bound complex. The study's collective findings underscore the structural stabilization of ligand-protein complexes, contributing valuable insights into the potential anti-Parkinson's properties of X. granatum. These discoveries hold promise for developing more effective therapies for Parkinson's disease and significantly contribute to the neurology field.